Improvement’s process of the network of science and technology organizations in Vietnam and orientations to enhance scienceindustry links: Historical milestones - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
The improvement and reform process of the network of science and technology (S&T) organizations in Vietnam has passed a long period, starting by Decision No. 175/CP of the Government dated 29th April 1981. Since that time, the State and Government promulgated numerous policy measures to improve and to reform the network to make it fit the process of socio-economic development of the country. This paper is focused on analysis of policy measures to improve and to reform the network of S&T organizations in Vietnam which are oriented to link better science and industries. Code: 14041401